The Potential Protective Mechanisms of Exercise-Responsive Molecules in Chronic Kidney Disease - Jae Seung Chang (운동과학)
PURPOSE Chronic kidney disease (CKD) is a major global health issue characterized by a gradual and irreversible decline in renal function. Despite its increasing prevalence, effective therapeutic options remain limited, highlighting the need for novel treatment approaches. This review highlights the importance of exercise as a nonpharmacological intervention by exploring the role of exercise-induced bioactive molecules in CKD management. METHODS An extensive literature review was conducted using PubMed, Scopus, Web of Science, and Google Scholar. The search terms included “myokine,” “exerkine,” “chronic kidney disease,” “nephropathy,” “renal function,” “podocyte,” “mesangial cell,” “exercise,” “physical activity,” and other related terms. RESULTS Exercise-induced molecules, particularly myokines and exerkines, can slow the progression of CKD through protective mechanisms. These molecules reduce oxidative stress via antioxidant defense pathways, regulate immune responses to limit inflammation, and inhibit fibrotic signaling by interacting with TGF-β and other pro-fibrotic factors. Furthermore, they preserve renal function by maintaining podocyte and mesangial cell integrity and modulating autophagy, thereby preventing kidney damage. CONCLUSIONS This review consolidates the current knowledge on the therapeutic potential and diverse functions of exercise-induced molecules in CKD, offering insights into their ability to slow disease progression and improve patient outcomes through nonpharmacological strategies.